Electromagnetic torque capabilities of permanent magnet flux-switching machine using modular rotor. Issue 1 (March 2021) - Soomro, Irfan Ali; Sulaiman, Erwan; Soomro, Hassan Ali; Amin, Faisal
Abstract: The use of a segmented rotor electric motor for lightweight electric vehicle applications has gained a lot of attention since the motor must have a high output torque and output power. Segmented rotor motors have performance indices that should be taken into consideration because not every machine is effective. Recently, permanent magnet flux switching machine (PMFSM) in salient rotor has become attractive for provide high torque and power. Undesirably, salient rotor inherited high iron loss and winding loss, Furthermore, PMFSM uses high PM volume and more flux leakage resulting in poor performance. This paper deals with a novel structure of modular rotor PMFSM with non-overlapping winding with minimal iron loss, high torque and high power. 2D finite element analysis (FEA) is used to investigate the performance of proposed motor in JMAG Designer 14.1. Three-phase operation of 12S/10P modular rotor PMFSM was designed and analysed based on the cogging torque, induced back emf, output torque and output power performances. The proposed motor securing the initial torque of 33.30 Nm and power of 12Kw at maximum current density of 30Arms/mm2. From the result it is concluded that modular rotor based PMFSM motor is suitable for light weight electric vehicles.